2022
DOI: 10.1002/mgg3.1877
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing and RNA analysis identify two novel CPLANE1 variants causing Joubert syndrome

Abstract: Background: Joubert syndrome (JS) is a genetically heterogeneous disorder; its genetic etiology involves more than 35 genes, and a limited number of studies have investigated the pathogenic mechanism of variants in patients with JS. RNA splicing analysis is critical to determine the functional significance for noncanonical splicing variants.Methods: Whole exome sequencing was performed to screen the causative gene variants in a JS family. Sanger sequencing was used to verify the variants. cDNA PCR products wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As analyzed by prediction software, the CPLANE 1 protein contains 2 coiled-coil domains and may be a transmembrane protein. However, most of the known CPLANE1 variants reported prior to 2015 are distributed outside the coiled-coil and transmembrane domains ( Fei et al, 2022 ). The Nordic JS cohort study ( Romani et al, 2015 ) showed that the proportion of CPLANE1 variants is 12% and that CPLANE1 variants are more likely to cause simplex JS, with the CPLANE1 gene having an 8.9% mutation rate in simplex JS ( Fleming et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As analyzed by prediction software, the CPLANE 1 protein contains 2 coiled-coil domains and may be a transmembrane protein. However, most of the known CPLANE1 variants reported prior to 2015 are distributed outside the coiled-coil and transmembrane domains ( Fei et al, 2022 ). The Nordic JS cohort study ( Romani et al, 2015 ) showed that the proportion of CPLANE1 variants is 12% and that CPLANE1 variants are more likely to cause simplex JS, with the CPLANE1 gene having an 8.9% mutation rate in simplex JS ( Fleming et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA extraction and phenotype‐driven whole exome sequencing (WES) were performed as previously described (Fei et al., 2022). Genomic DNA was isolated from peripheral blood lymphocytes of the proband (II2).…”
Section: Methodsmentioning
confidence: 99%